Three-dimensional porous Zn2VO4/ZnO/C thin film anode materials for high-performance Li-ion batteries. (June 2019) - Zhou, Jiafeng; Zhao, Bangchuan; Bai, Jin; Fang, Zhitang; Li, Kunzhen; Ma, Hongyang; Dai, Jianming; Zhu, Xuebin; Sun, Yuping
Abstract: A new type of Zn2 VO4 /ZnO/carbon composite (three-dimensional porous architecture) was firstly fabricated on a Ni-metal foam substrate thorough a facile electrostatic spray deposition (ESD) method followed by a calcination process. As a binder-free electrode in high performance lithium-ion batteries (LIBs), the composite electrode displays an outstanding long cycling performance, and it exhibits a high specific capacity of 930.8 mAh g −1 at 2 A g −1 even after 800 cycles without any capacity fading. And, the composite also shows a good rate performance with specific charge capacities of 742.1, 658.7, 804.9, 567.3 and 519.3 mAh g −1 at 0.1, 2, 5, 10 and 12 A g −1, respectively. Graphical abstract: Unlabelled Image